2016
DOI: 10.1371/journal.pone.0166463
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Dependence of the Pulmonary Resistance x Compliance (RC) Time and Impact on Right Ventricular Load

Abstract: BackgroundThe effect of heart rate (HR) and body surface area (BSA) on pulmonary RC time and right ventricular (RV) load is unknown.MethodsTo determine the association of HR and BSA with the pulmonary RC time and measures of RV load, we studied three large patient cohorts including subjects with 1) known or suspected pulmonary arterial hypertension (PAH) (n = 1008), 2) pulmonary hypertension due to left heart disease (n = 468), and 3) end-stage heart failure with reduced ejection fraction (n = 150). To corrobo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“…Anemia-driven increases in heart rate can adversely affect RV afterload, with increased work for the RV spurring compensatory remodeling. 47 The augmented RV end diastolic pressure observed in SS chimeras with 3 weeks of SMC CYB5R3 knockdown is consistent with an elevated RV preload that one expects with anemia. 48,49 Although the monogenetic defect of sickle cell anemia, resulting in substitution of valine for glutamic acid in the codon for b-globin synthesis, is certainly the origin of the anemia that drives much of the multiorgan pathology known to characterize the disease, the degree of proximity with which that anemia affects ventricular remodeling or function on either side of the heart remains unclear.…”
Section: Discussionsupporting
confidence: 54%
“…Anemia-driven increases in heart rate can adversely affect RV afterload, with increased work for the RV spurring compensatory remodeling. 47 The augmented RV end diastolic pressure observed in SS chimeras with 3 weeks of SMC CYB5R3 knockdown is consistent with an elevated RV preload that one expects with anemia. 48,49 Although the monogenetic defect of sickle cell anemia, resulting in substitution of valine for glutamic acid in the codon for b-globin synthesis, is certainly the origin of the anemia that drives much of the multiorgan pathology known to characterize the disease, the degree of proximity with which that anemia affects ventricular remodeling or function on either side of the heart remains unclear.…”
Section: Discussionsupporting
confidence: 54%
“…This makes a significant drug contribution of beta blockade in the Obese+ePVH group unlikely. Recent evidence suggests that reduction in tachycardia, observed in the Obese+ePVH group on exercise, may act to reduce RV pulsatile loading and thus total afterload (Metkus et al 2016 ). We cannot therefore discount the possibility of both detrimental and beneficial effects of beta blockade on RV and pulmonary vascular exercise responses in our Obese+ePVH cohort.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies showed recently that PVR and PAC are inversely related, and RC-time is constant over a wide range of severities, aetiologies and treatments of PH (figure 3) [41, 45, 46]. It is noteworthy that RC-time is decreased when PAWP increases in patients with heart failure [47, 48]. The fact that PVR takes the wedge pressure into account, whereas compliance, calculated as SV/PP, does not, gives rise to an altered RC-time in post-capillary PH.…”
Section: Assessment Of the Pulmonary Circulation In A Heart-independementioning
confidence: 99%